ANALISIS STRATEGI PENGEMBANGAN USAHA DENGAN PENGGUNAAN QRIS SEBAGAI METODE PEMBAYARAN UMKM DI KOTA DEPOK - Titik Purwinarti; Yanita Ella Nilla Chandra; Bunga Safira Adhliana; Rena Yolanda, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
This study aims to analyze the MSME culinary business development strategy in the city of Depok by utilizing the Indonesian Standard Quick Response (QRIS) digital payment as an opportunity to increase sales. This study uses qualitative research methods with descriptive analysis and SWOT analysis. Collecting data using interviews and direct observation. The results of the study indicate that MSME actors need to add digital payment services using QRIS as one of the promotions and sales strategies in competition in the digital era, MSME actors as the largest contributor to GDP in Indonesia need to have the ability and desire to continue to adapt so that their business continues to grow. such as lack of ability due to knowledge and age factors must be overcome by providing counseling or learning to MSME actors.